Pengelompokan Kabupaten/Kota Di Provinsi Papua Berdasarkan Indikator Kesejahteraan Rakyat 2020 - Ragil Chelvin Pratama; Nasrudin Nasrudin (Politeknik Statistika STIS, 2022)
In 2020, Papua's Human Development Index (HDI) lags behind other provinces and there is gap between districts/cities. However, the HDI does not provide broad welfare information, so an indicator that can provide information from a broad perspective is needed, namely the people's welfare indicator by the Central Statistics Agency (BPS). This study aims to look at welfare through the grouping of regencies/cities in Papua Province based on people's welfare indicators and provide a profile of the cluster formed from the best method. Data sourced from publications and website BPSThe grouping uses cluster analysis with single linkage, average linkage, complete linkage, Ward's, and k-means methods. The results show that there are welfare inequality from various dimensions of district/city welfare in Papua. The best method is Ward's with four cluster results. Cluster 1 is economically prosperous, consisting of eleven districts/cities, cluster 2 is prosperous in employment, consisting of eight districts, cluster 3 is prosperous in health, consisting of six districts, and cluster 4 is prosperous in other social dimensions, consisting of four districts.